Surgical Management of Congenital Rectovaginal Fistula and Type III Atresia Ani in an Umbalachery Calf - Uma, R; TamilMahan, T (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A two day old Umbalacheri calf was referred to Teaching Veterinary Clinical Complex, Veterinary College and Research Institute, Orathanadu, Tamil Nadu with a complaint of passing dung through external genitalia since birth and it was treated by a local veterinarian with vain. Clinical examination revealed, passage of dung through vulva and a wound in the anal region inflicted by the local veterinarian. Per vaginal examination revealed 1.5 inches long fistula at the dorsal aspect of vagina at about 1.5 inches cranial to the vulva. There was no bulging of perineal region on pressing the abdomen indicating type III Atresia Ani. All the physiological and biochemical values were within the normal limits. Based on the history, clinical signs and physical examination, the case was diagnosed as rectovaginal fistula with Type III Atresia Ani and reconstructive surgery was opted to correct the condition.